2002
DOI: 10.1080/00015458.2002.11679277
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Lymphadenopathy in Adults: a Review of 35 Cases

Abstract: We retrospectively reviewed clinical, diagnostic, therapeutic and prognostic features of 35 patients (25 female, 10 male, mean age: 33 years, range: 16-70) with tuberculous lymphadenopathy (TB LAP) which had been followed since 1980. The diagnosis was established by tissue sampling in 32 cases (caseating granulomatous adenitis in 89%) or presence of acid-fast bacilli (AFB) in the aspirate in 2 cases and in the drainage in 1 case. Paraffin-embedded granulomatous tissues were stained by Ehrlich-Ziehl-Neelsen (EZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…Mert et al [23] demonstrated a delay between development of TBLA and admission from 15 to 730 days among 35 Turkish TBLA cases. No mean value was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mert et al [23] demonstrated a delay between development of TBLA and admission from 15 to 730 days among 35 Turkish TBLA cases. No mean value was reported.…”
Section: Resultsmentioning
confidence: 99%
“…The case definition of TBLA was inconsistent in the different studies with specimens examined with microscopy, culture, polymerase chain reaction, and pathology, and/or cases based on clinical assessment. Most samples were collected using fine-needle aspiration (FNA) and/or excisional biopsy [19, 20, 23-29]. A single article had no information on the type of biopsy [21], while another study used bronchoalveolar lavage fluid, lumbar puncture, paracentesis of ascites fluid, and surgically obtained abdominal biopsies [22].…”
Section: Resultsmentioning
confidence: 99%
“…The lymph nodes can be infected by Mycobacterium through hematogenous route or by a local extension from tuberculous infection of adenotonsillar tissue. [13] Thyroglossal duct cysts are the most common congenital neck masses with a typical presentation as a painless cystic mass or fistula in the region of hyoid bone at or near the midline. Due to the process of embryogenesis, thyroglossal duct cysts can be found at the base of the tongue to the lower midline of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphadenitis is the most common presentation of extra pulmonary TB (1,2) and the cervical lymph nodes are most frequently involved (3). In the developing world, TB is responsible for up to 43% of the peripheral lymphadenopathy (4).…”
mentioning
confidence: 99%